Radical TADF: Quartet-Derived Luminescence with Dark TEMPO. - Gorgon, Sebastian; Murto, Petri; Congrave, Daniel G; Matasovic, Lujo; Bond, Andrew D; Riesgo-Gonzalez, Victor; Myers, William K; Bronstein, Hugo; Friend, Richard H (Wiley, 2025)
High-spin states in organic molecules offer promising tuneability for quantum technologies. Photogenerated quartet excitons are an extensively studied platform, but their applications are limited by the absence of optical read-out via luminescence. Here, a new class of synthetically accessible molecules with quartet-derived luminescence is demonstrated, formed by appending a non-luminescent TEMPO radical to thermally activated delayed fluorescence (TADF) chromophores previously used in OLEDs. The low singlet-triplet energy gap of the chromophore opens a luminescence channel from radical-triplet coupled states. A set of design rules is established by tuning the energetics in a series of compounds based on a naphthalimide (NAI) core. Generation of quartet states is observed and the strength of radical-triplet exchange is measured. In DMAC-TEMPO, up to 72% of detected photons emerge after reverse intersystem crossing from the quartet state repopulates the state with singlet character. This design strategy does not rely on a luminescent radical to provide an emission pathway from the high-spin state. The large library of TADF chromophores promises a greater pallet of achievable emission colours.
Publication status: Published
Funder: Emmanuel College, Cambridge
Keywords: TADF; electron spin; luminescence; optoelectronics; organic chromophores; quartet states